MENGELOLA KEKUATAN MEREK DAN ALIANSI STRATEGIS: INOVASI DALAM PEMASARAN SPONSORSHIP PADA EVENT KUSTOM KULTURE DI INDONESIA - Nashrudin Latif; Suharyanto Suharyanto; I Made Bagus Dwiarta (J-MACC, 2025)
The vital role of events lies in the power of sponsorship. The relationship between sponsorship (supporters) and consumer response has been a subject of marketing relationship management studies, but there has been little research from the perspective of sponsorship (sponsors). The purpose of this study is to explore, from the perspective of sponsorship, the relationship between sponsors and sponsees at custom culture events in Indonesia using the concepts of brand alliance and relationship marketing. A qualitative research method with a case study approach was used to expand the scope of knowledge of relationship management in the entertainment industry in event sponsorship and information for the event industry and professionals. The results of the study found important points regarding the effectiveness of relational marketing management, which includes event strategy, cross-organizational culture building, positive relationships between individuals, and relationship stability as attributes of successful sponsorship relationship management.